Antecedents of Customer Experience Value on Halal Cosmetics Products in Malaysia. - Bee Li, Yeo (2018)
This study focuses on the determinants of customers‟ satisfaction in the Malaysian for Halal cosmetics products. This study conceptualises consumption values as a multi-dimensional construct which consists of six dimensions of values, i.e. functional value, social value, emotional value, conditional value, epistemic value and religiosity value. This study examines both rational states and emotional states of the consumers by studying the relationships between consumption values, consumers‟ experience and customers‟ satisfaction toward Halal cosmetics product. The sampling consists of 359 Muslim and non-Muslim consumers from the urban states of Peninsular Malaysia which comprises Wilayah Persekutuan (KL, Putrajaya and Labuan), northern states (Perlis, Perak, Kedah and Pulau Pinang), southern states (Melaka and Johor), western states (Negeri Sembilan and Selangor), east coast (Pahang, Terengganu and Kelantan), Sabah and Sarawak were collected and analysed using Structural Equation Modelling (SEM PLS 3.0). Out of the 7 hypotheses tested, four are supported. The analysis revealed positive relationships between functional value, social value, emotional value and consumer experience value toward customer satisfaction for consuming the Halal cosmetics product. Furthermore the result also demonstrated that both Muslim and non-Muslim consumers are satisfied purchasing the Halal cosmetics product. The study also highlights the implications and limitations of the study as well as the suggestions for future research.